Feasibility of physiologist-led stress echocardiography for the assessment of coronary artery disease. Issue 2 (June 2017) - Khan, Jamal N; Griffiths, Timothy; Fatima, Tamseel; Michael, Leah; Mihai, Andreea; Mustafa, Zeeshan; Sandhu, Kully; Butler, Robert; Duckett, Simon; Heatlie, Grant
Abstract : Background: Physiologist-led stress echocardiography (PLSE) services provide potential for expansion of SE services and increased productivity for cardiologists. There are however no published data on the feasibility of PLSE. We sought to assess the feasibility, safety and robustness of PLSE and cardiologist-led stress echocardiography (CLSE) for coronary artery disease (CAD) assessment. Methods: Retrospective analysis of 898 patients undergoing PLSE or CLSE for CAD assessment using exercise or dobutamine stress over 24 months. PLSE involved 2 cardiac physiologists (exercise) or 1 physiologist plus 1 cardiac nurse (dobutamine). A cardiology registrar was present in the echocardiography department during PLSE in case of medical complications. CLSE involved 1 physiologist and 1 trainee cardiologist who analysed the study and reviewed findings with an imaging cardiologist. Sixteen-segment wall motion scoring (WMS, WMSI) analysis was performed. Feasibility (stressor, image quality, proportion of completed studies, agreement with imaging cardiologist analysis) and safety (complication rate) were compared for PLSE and CLSE. Results: The majority of studies were CLSE (56.2%) and used dobutamine (68.7%). PLSE more commonly used exercise (69.2%). Overall, 96% of studies were successfully completed (>14 diagnostic segments in 98%, P  = 0.899 PLSE vs CLSE). Commencement of PLSE was associated with an increase in annual SE's performed for CAD assessment. Complication rates were comparably very low for PLSE and CLSE (0.8% vs 1.8%, P  = 0.187). There was excellent agreement between PLSE and CLSE WMS interpretation of 480 myocardial segments at rest ( κ  = 0.87) and stress ( κ  = 0.70) and WMSI (ICCs and Pearson's r >0.90, zero Bland–Altman mean bias). Conclusion: This to our knowledge is the first study of the feasibility of PLSE. PLSE performed by well-trained physiologists is feasible and safe in contemporary practice. PLSE and CLSE interpretation of stress echocardiography for CAD agree very closely.